2023
DOI: 10.1021/acschemneuro.2c00720
|View full text |Cite
|
Sign up to set email alerts
|

8-20 Fragment as an Anti-Fibrillogenic and Neuroprotective Agent: Advancing toward Efficient Alzheimer’s Disease Treatment

Abstract: Alzheimer’s disease (AD) is the most common cause of dementia, characterized by a spectrum of symptoms associated with memory loss and cognitive decline with deleterious consequences in everyday life. The lack of specific drugs for the treatment and/or prevention of this pathology makes AD an ever-increasing economic and social emergency. Oligomeric species of amyloid-beta (Aβ) are recognized as the primary cause responsible for synaptic dysfunction and neuronal degeneration, playing a crucial role in the onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…We hypothesized that this unexpected behavior could be ascribed to small amount of Aβ1‐40 fragments present in the sample and generated by peptide degradation. This hypothesis agrees with literature data demonstrating that several Aβ fragments are effectively able to inhibit fibril formation for both Aβ1‐40 and Aβ1‐42 [53–55] . Considering these results, only highly pure samples (>95 %) were used in our analysis.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…We hypothesized that this unexpected behavior could be ascribed to small amount of Aβ1‐40 fragments present in the sample and generated by peptide degradation. This hypothesis agrees with literature data demonstrating that several Aβ fragments are effectively able to inhibit fibril formation for both Aβ1‐40 and Aβ1‐42 [53–55] . Considering these results, only highly pure samples (>95 %) were used in our analysis.…”
Section: Methodssupporting
confidence: 91%
“…This hypothesis agrees with literature data demonstrating that several Aβ fragments are effectively able to inhibit fibril formation for both Aβ1-40 and Aβ1-42. [53][54][55] Considering these results, only highly pure samples (> 95 %) were used in our analysis. However, additional studies will be undertaken to further explore this issue.…”
Section: Analysis Of 26-o-acyl Iso Aβ1-40 Isomerization To Aβ1-40mentioning
confidence: 99%
“…2 Despite numerous studies and clinical trials focused on AD, no currently available drugs are capable of alleviating its symptoms. 3 Therefore, it is crucial to implement preventive measures to reduce the incidence of AD by addressing neuroinflammation and oxidative stress during the aging process. 4 Recent studies have reported that dysregulation of the gut microbiota is directly or indirectly linked to cognitive function, and the gut−brain axis could improve cognitive injury by regulating gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence suggests that oxidative stress and neuroinflammation can activate microglia, an early symptom in the development of Alzheimer’s disease (AD) . Despite numerous studies and clinical trials focused on AD, no currently available drugs are capable of alleviating its symptoms . Therefore, it is crucial to implement preventive measures to reduce the incidence of AD by addressing neuroinflammation and oxidative stress during the aging process …”
Section: Introductionmentioning
confidence: 99%
“…[7] Current preclinical and clinical AD drugs primarily aim to the reduction of Aβ production, prevention of Aβ aggregation, and promotion of Aβ clearance. [8] Recent studies have explored strategies to reduce Aβ neurotoxicity by altering the amino acid structures within the Aβ sequence, [9] particularly through catalytic photooxygenation of Aβ approaches. [10] However, these earlier studies have predominantly depended on the use of external physical light sources, resulting in limited light penetration of brains and posing a challenge for future clinical applications.…”
Section: Introductionmentioning
confidence: 99%